ANESTHESIA AND ANALGESIA IN ANTARCTIC FISH: AN EXPERIMENTAL APPROACH - BASTOS-RAMOS, WILMA PEREIRA; GONÇALVES, NEUZA M. F. M.; BACILA, METRY (Archives of Veterinary Science, 1998)
Foi levado a efeito em peixes antárticos um estudo sobre as ações anestésicas e/ou analgésicas de depressores centrais ketamine, fentanyl e thiopental bem como do anestésico local benzocaina. As drogas foram adicionadas à água marinha aerada nas temperaturas de 1 a 1,5oC. Ketamine (15 mg/L) e fentanyl (50 g/L) não induziram anestesia mas causaram demorada analgesia e sedação. Doses de 100 mg/L de Thiopental foram necessárias para anestesiar peixes, ou seja, em concentração 30 vezes maior do que a dose anestésica usual utilizada para mamíferos. A anestesia ocasionada nos peixes foi longa - de 3 a 4 horas - e difícil de ser controlada. Um dos peixes utilizados na experimentação permaneceu em estado de comatose por quatro dias com sobrevida. Benzocaina em doses de 100 mg/L foi eficiente para anestesiar peixes dentro de 6 a 8 minutos após a sua administração. A anestesia, neste caso, teve duração de 15 a 20 minutos acompanhada de pequena depressão respiratória. Abstract It was studied in Antarctic fishes the anesthetic and/or analgesic actions of central depressors ketamine, fentanyl and thiopental as well as the local anesthetic benzocaine. The drugs were added to aerated marine water at temperatures of 1-1.5 C. Ketamine (15 mg/L) and fentanyl (50 g/L) failed in inducing anesthesia but caused a long lasting analgesia and sedation. Thiopental was required in doses of 100 mg/L to anesthetize the fishes, that is, about 30 times higher than the usual anesthetic dose for mammals. The anesthesia was long lasting, that is, 3-4 h, and difficult to control. One fish remained in a comatose state for four days with survival. Benzocaine in doses of 100 mg/L was successful in anesthetizing the fishes within 6-8 min, anesthesia lasting for 15-20 min, with a minor respiratory depression.